Site- and energy-selective slow-electron production through intermolecular Coulombic decay - Gokhberg, Kirill; Kolorenč, Přemysl; Kuleff, Alexander I.; Cederbaum, Lorenz S. (Nature, 2014)
Intermolecular Coulombic decay driven by resonant Auger decay can be used to produce low-energy electrons selectively from chosen molecular or atomic sites and with tunable energies, with possible applications in radiation therapy.
Published online 22 December 2013
Gesehen am 12.10.2020